Exploring Rubric-Related Multidimensionality in Polytomously Scored Test Items. (May 2017) - Bolt, Daniel M.; Adams, Daniel J.
Test items scored as polytomous have the potential to display multidimensionality across rating scale score categories. This article uses a multidimensional nominal response model (MNRM) to examine the possibility that the proficiency dimension/dimensional composite best measured by a polytomously scored item may vary by score category, an issue not generally considered in multidimensional item response theory (MIRT). Some practical considerations in exploring rubric-related multidimensionality, including potential consequences of not attending to it, are illustrated through simulation examples. A real data application is applied in the study of item format effects using the 2007 administration of Trends in Mathematics and Science Study (TIMSS) among eighth graders in the United States.